Penguatan Komisi Kepolisian Nasional Dalam Pengawasan Penyidikan Tindak Pidana Oleh Polri - Rahman Amin; Muhammad Fikri Al Aziz (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Changes since the separation of the Indonesian National Police from the ABRI include institutional, substantive and cultural aspects, marked by the passage of the law on the Indonesian National Police as the legal basis for the Indonesia National Police to become an independent and professional institution. However, the reform of the Indonesia National Police from the cultural aspect has not been carried out as expected, especially in law enforcement, cases are still handled unprofessionally and contrary to legal provisions so that external supervision, one of which is by national police commission, is important. This research is normative juridical, with a statutory approach, where secondary data is obtained through library research, and is supported by primary data from the field. This study aims to determine the current condition of national police commission, and how national police commission will be strengthened in the future in the supervision of criminal investigations by the Indonesia National Police. The results of the research, that there are still many weaknesses in national police commission, namely the position of national police commission which was formed as an advisory institution placed under the President, the formation of national police commission is only based on a Presidential Regulation with limited duties and authorities, the legal culture of Indonesia National Police members who do not fully understand the duties and functions of national police commission, human resources are still lacking, infrastructure is inadequate, and budget allocations cannot meet national police commission’s workload.Strengthening national police commission in the future through institutional changes to national police commission as an independent external monitoring institution for Indonesia National Police, strengthening the legal basis for establishing national police commission with laws, building a legal culture for Indonesia National Police members by increasing understanding of the duties and functions of national police commission, increasing the number of national police commission employees with appropriate competencies needs, provide infrastructure in the form of office buildings and adequate facilities, and increase the amount of the budget in accordance with the workload faced by national police commission.